From Conventional To Islamic Finance: Implications For Financial Inclusion In Aceh - Dira Abdi (Gabungan Riset Edukasi dan Ekplorasi Teori (GREET), 2025)
The transition from conventional to Islamic finance in Aceh represents a unique case of financial system transformation driven by religious, cultural, and regulatory imperatives. This study examines the drivers, challenges, and outcomes of this transition, with a specific focus on its implications for financial inclusion. Employing a mixed-methods design, the research integrates qualitative interviews with policymakers, bank managers, and community leaders, alongside survey data from 200 residents across urban and rural settings. Findings reveal that Islamic finance, anchored in Shariah principles, has expanded access to financial services for underserved groups, particularly women and micro-entrepreneurs, through microfinance programs and risk-sharing mechanisms. The establishment of the Aceh Shariah Financial Authority has strengthened governance, enhanced public trust, and facilitated a 30% increase in Islamic banks since 2020. However, challenges remain, including uneven literacy, misconceptions about Islamic finance, and gaps in technological adoption. The study contributes to the literature by highlighting Aceh’s distinctive socio-religious context, while offering insights into the role of regulation, innovation, and education in advancing financial inclusion. The findings suggest that Aceh’s experience can serve as a reference model for regions seeking ethical and culturally embedded approaches to inclusive financial development.